Explaining participation rates in recreational fishing across industrialised countries - Arlinghaus, R.; Tillner, R.; Bork, M. (Fisheries management and ecology, 2015)
On average, 10.52% of the total population was found to fish for recreation across the industrialised world (N = 27 countries), amounting to an estimated 118 million (95% confidence interval 81–154 million) people in North America, Europe and Oceania. Participation rates declined with population density and gross domestic product, indicating a negative effect of urbanisation and post‐modernisation on fishing interest. Participation rates also declined with increasing median age, average household size and unemployment rate, suggesting resource limitation to constrain participation in fishing. By contrast, two indicators of the cultural importance of fish (fish landings and per capita fish consumption) and an indicator of perceived need for leisure (weekly working hours) were positively correlated with fishing participation. Based on these findings, which explained 60% of the variance in fishing participation across the industrialised world, reduced fishing interest is to be expected with post‐industrialisation. Dedicated management and marketing intervention is needed to reverse the track of diminishing fishing interest in industrialised countries.